2019
DOI: 10.1215/03616878-7367036
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality, Depression, and Voter Turnout

Abstract: Context: This article untangles the effects of depression on voter turnout among blacks and whitesand among women and men and considers several factors-income, health insurance, church attendance, group consciousness, and empowerment-that may mitigate the negative effects of depression on turnout. Methods: The authors estimated regression models of voter turnout on depression across race and gender groups using data from the Panel Study of Income Dynamics and the National Longitudinal Study of Adolescent to Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
(47 reference statements)
2
12
1
Order By: Relevance
“…Ojeda (2015) provided the first evidence for the negative effect of depression on turnout and political participation, finding that episodes of depression during youth have lasting negative effects on participation in later years. Since then, studies have examined how depression slows the development of a voting habit (Ojeda and Pacheco 2017), analyzed how self-reported mental health dampens or spurs participation at different levels of government (Couture and Breux 2017), and assessed racial and gendered differences in how depression reduces turnout (Ojeda and Slaughter 2019). Given the small number of studies, the typical focus on turnout among young adults in the United States, and the emphasis on establishing a correlation between depression and turnout (rather than identifying and testing mechanisms), a number of questions remain.…”
Section: Hypothesesmentioning
confidence: 99%
“…Ojeda (2015) provided the first evidence for the negative effect of depression on turnout and political participation, finding that episodes of depression during youth have lasting negative effects on participation in later years. Since then, studies have examined how depression slows the development of a voting habit (Ojeda and Pacheco 2017), analyzed how self-reported mental health dampens or spurs participation at different levels of government (Couture and Breux 2017), and assessed racial and gendered differences in how depression reduces turnout (Ojeda and Slaughter 2019). Given the small number of studies, the typical focus on turnout among young adults in the United States, and the emphasis on establishing a correlation between depression and turnout (rather than identifying and testing mechanisms), a number of questions remain.…”
Section: Hypothesesmentioning
confidence: 99%
“…Nevertheless, the negative effect is not restricted to seniors. Population-level survey studies have shown how poor physical or mental health depresses voting in Ireland (Denny and Doyle, 2007a), in the UK (Denny and Doyle, 2007b;Rapeli et al, 2019), in Europe in general (Mattila et al, 2013), in Canada (Couture and Breux, 2017), in the Nordic countries (Söderlund and Rapeli, 2015) and in the USA (Gollust and Rahn, 2015;Pacheco and Fletcher, 2015;Burden et al, 2017;Ojeda and Slaughter, 2019). The results somewhat vary depending on the country or type of election concerned, but generally the difference in turnout is about 10 percentage points between the opposite ends of the five-point SRH scale.…”
Section: Forms Of Participation and Healthmentioning
confidence: 99%
“…So far, much of this has focused on behaviour. We know, for example, that turnout is lower among voters with poor physical health (Schur et al 2002;Mattila et al 2013;Pacheco & Fletcher 2015) or poor mental health -including depression (Ojeda 2015;Sund et al 2017;Burden et al 2017;Couture & Breux 2017;Ojeda & Pacheco 2019;Ojeda & Slaughter 2019). Yet to date we know very little about the impact of psychological health on political attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…2017; Burden et al. 2017; Couture & Breux 2017; Ojeda & Pacheco 2019; Ojeda & Slaughter 2019). Yet to date we know very little about the impact of psychological health on political attitudes.…”
Section: Introductionmentioning
confidence: 99%